Theoretical Foundations of Witness Immunity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes issues related to the theoretical foundations of witness immunity. Most importantly, emphasis is placed on the issues of the institution of immunity in criminal proceedings and ensuring the rights and legitimate interests of certain categories of persons. In this article, along with national and foreign legislation, the opinions of scientists are also analyzed.